Front Cover Picture: Pyrazoleamides in Catalytic Asymmetric Reactions: Recent Advances (Adv. Synth. Catal. 14/2021). Issue 14 (1st June 2021) - Meninno, Sara; Franco, Francesca; Benaglia, Maurizio; Lattanzi, Alessandra
Abstract : The front cover picture, designed by Sara and Luca Meninno, illustrates poorly reactive carboxylic acids and their ester and amide derivatives transformed into pyrazoleamides super‐molecules with superpowers. Where carboxylic acids, esters and amides fail pyrazoleamides succeed, allowing the transition from a world with limited possibilities to a rich and futuristic world, meeting the increasing needs of the society. The super‐powers consist in: i) easy one‐step synthesis from readily available carboxylic acids; ii) easy metal and H‐bonding coordination with catalysts, unlocking otherwise inaccessible reactions on carboxylic acid derivatives; iii) exceptional leaving group ability which enables several post‐functionalizations with different nucleophiles. Pyrazoleamides, unlike carboxylic acid derivatives have proven increasingly useful starting materials in a variety of diastereo‐ and enantioselective metal‐, organocatalytic and photoinduced transformations, giving access to valuable intermediates, heterocycles and pharmaceuticals. Details can be found in the Review by Meninno, Franco, Benaglia, and Lattanzi. (S. Meninno, F. Franco, M. Benaglia, A. Lattanzi, Adv. Synth. Catal . 2021, 363, 3380–3410; DOI: 10.1002/adsc.202100006 )